2022
DOI: 10.3390/molecules27238261
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dispersed Ni Nanoclusters Spontaneously Formed on Hydrogen Boride Sheets

Abstract: Hydrogen boride (HB) sheets are two-dimensional materials comprising a negatively charged hexagonal boron network and positively charged hydrogen atoms with a stoichiometric ratio of 1:1. Herein, we report the spontaneous formation of highly dispersed Ni nanoclusters on HB sheets. The spontaneous reduction reaction of Ni ions by the HB sheets was monitored by in-situ measurements with an ultraviolet-visible spectrometer. Acetonitrile solutions of Ni complexes and acetonitrile dispersions of the HB sheets were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The small diffraction peaks at 27.5°and 28°for the HB-r60 and HB-r90 samples, respectively (Figure S1b, Supporting Information), might originate from unknown by-products and/or stacked HB sheets. [29] The temperature-programmed desorption (TPD) curves (Figure 2a) contain a broad peak up to 1400 K for all samples, consistent with previous reports of HB sheets, [17,21,22,23,24] as well as peaks at 430, 500, and 550 K. The intensity of the 400 K peak was higher for samples with larger XRD peaks, suggesting that the 400 K peak originates from the unknown byproduct and/or stacking of the HB sheets. The TPD peak intensity at 500 K slightly decreased with the volume of resin, whereas the peak at 550 K slightly increased, indicating that the B-H bond becomes stronger in samples prepared with higher volumes of resin.…”
Section: Controlling B-h-b and Terminal B-h Bond Populationsupporting
confidence: 88%
See 2 more Smart Citations
“…The small diffraction peaks at 27.5°and 28°for the HB-r60 and HB-r90 samples, respectively (Figure S1b, Supporting Information), might originate from unknown by-products and/or stacked HB sheets. [29] The temperature-programmed desorption (TPD) curves (Figure 2a) contain a broad peak up to 1400 K for all samples, consistent with previous reports of HB sheets, [17,21,22,23,24] as well as peaks at 430, 500, and 550 K. The intensity of the 400 K peak was higher for samples with larger XRD peaks, suggesting that the 400 K peak originates from the unknown byproduct and/or stacking of the HB sheets. The TPD peak intensity at 500 K slightly decreased with the volume of resin, whereas the peak at 550 K slightly increased, indicating that the B-H bond becomes stronger in samples prepared with higher volumes of resin.…”
Section: Controlling B-h-b and Terminal B-h Bond Populationsupporting
confidence: 88%
“…The intensity of the light source of the UV–vis device was measured beforehand to obtain a reliable wavelength range for the UV–vis measurements. [ 29 ] UV–vis spectra of the HB sheets in acetonitrile at higher HB concentrations (0.02–12.70 mol L −1 ) were measured by the EEM apparatus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Several studies have confirmed that HB sheets exhibit semimetal electronic properties, 14 superior catalytic properties, [15][16][17][18][19] and specific reductant properties. 17,20,21 Fujino et al demonstrated the ability of HB sheets to catalyze the production of ethylene from ethanol with high selectivity and long-term stability. 15,16 Similarly, Gao et al found that a catalyst prepared with HB and Pt exhibited superior electrocatalytic activity and stability against oxygen reduction compared to commercial Pt/C for proton exchange membrane fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…22 HB sheets have redox potentials between À0.277 and À0.257 V versus the standard hydrogen electrode, enabling them to selectively reduce metal ions in solution and form nanoclusters on the sheets. 20,21 This property makes HB sheets useful as reducing agents. Moreover, ultraviolet (UV) irradiation at 300 K can cause H 2 to be released from the HB sheets as a decomposition product, 23 making them a controllable source of H 2 emission.…”
Section: Introductionmentioning
confidence: 99%